Computational investigation of a covalent triazine framework (CTF-0) as an efficient electrochemical sensor. Issue 7 (31st January 2022) - Sarfaraz, Sehrish; Yar, Muhammad; Ans, Muhammad; Gilani, Mazhar Amjad; Ludwig, Ralf; Hashmi, Muhammad Ali; Hussain, Masroor; Muhammad, Shabbir; Ayub, Khurshid
Abstract : In the current study, a covalent triazine framework (CTF-0) was evaluated as an electrochemical sensor against industrial pollutants i.e., O3, NO, SO2, SO3, and CO2 . Abstract : In the current study, a covalent triazine framework (CTF-0) was evaluated as an electrochemical sensor against industrial pollutants i.e., O3, NO, SO2, SO3, and CO2 . The deep understanding of analytes@CTF-0 complexation was acquired by interaction energy, NCI, QTAIM, SAPT0, EDD, NBO and FMO analyses. The outcome of interaction energy analyses clearly indicates that all the analytes are physiosorbed onto the CTF-0 surface. NCI and QTAIM analysis were employed to understand the nature of the non-covalent interactions. Furthermore, SAPT0 analysis revealed that dispersion has the highest contribution towards total SAPT0 energy. In NBO analysis, the highest charge transfer is obtained in the case of SO3 @CTF-0 (−0.167 e − ) whereas the lowest charge transfer is observed in CO2 @CTF-0. The results of NBO charge transfer are also verified through EDD analysis. FMO analysis revealed that the highest reduction in the HOMO–LUMO energy gap is observed in the case of O3 (5.03 eV) adsorption onto the CTF-0 surface, which indicates the sensitivity of CTF-0 for O3 analytes. We strongly believe that these results might be productive for experimentalists to tailor a highly sensitive electrochemical sensor using covalent triazine-based frameworks (CTFs).